Deploying Heritage-Led Urban Regeneration: Three Cases from Skopje - Ivanovski, Jovan; Ivanovska Deskova, Ana (TU Delft / Faculty of Architecture and the Built Environment, 2020)
Like many other urban settlements located on a crossroad of important transport and trade routes, the city of Skopje faced turbulent times throughout its history. As a result of a dynamic exchange of cultures, the urban fabric contains overlapped architectural layers from different historical origins: Roman, Byzantine, Ottoman, Pre-Modern, Modern, Post-socialist… Despite the fact that the most recent, 20th century architectural layer is the most visible one, there are city fragments that carry matrices related to older historical periods. An example of this are the Old Bazaar and the Medieval Fortress. Regardless of their institutional protection, today they are facing complex challenges. They are related to their administration, quality of conservation and restoration policies, with the outdated and, at times, obsolete program they provide. The aim of this paper is to present recent efforts to introduce a sequence of contemporary, heritage-led regeneration initiatives. New acupunctural interventions have been envisaged as a part of the Horizon 2020 Project (ROCK – Regeneration and Optimization of Cultural Heritage in Creative and Knowledge Cities), involving local municipalities, the University and various stakeholders. The establishing of the Urban Living Lab in the middle of the traditional tissue of the Old Bazaar has provided a hub for various cultural activities: presentations, lectures, exhibitions, discussions among professionals and the wider audience. The project “Kale – Art Fortress” has a tendency to activate the public space between the Museum of Contemporary Art and the Medieval Fortress through a sequence of small temporary structures. The segment entitled “Lost Ambiences” virtually recreates the buildings and urban ambiences that no longer exist in the physical presence of the Old Bazaar.
Keywords: Cultural heritage, urban regeneration, stakeholders